Competing on freemium: Digital competition with network effects - Boudreau, Kevin J.; Jeppesen, Lars Bo; Miric, Milan (Strategic Management Journal, 2022)
Abstract Research Summary “Freemium” product strategies—where a free basic version of a product is offered alongside a full “premium” paid version—are often used by companies to attempt to increase the size of their user base and benefit from network effects. However, there is limited empirical evidence of how using freemium strategies impacts firm revenues. We empirically investigate how the strengthening of network effects on the Apple App Store influenced product sales of firms using freemium strategies, contrasting the impacts on both market leaders and followers. We find that stronger network effects did not on their own lead to greater revenues for market leaders with respect to followers. However, in settings where freemium strategies were used, network effects greatly amplified the advantage of leaders over followers. Managerial Summary Freemium strategies are increasingly common as a way for firms to increase the number of users and benefit from network effects. However, there has not been much empirical investigation in this regard, particularly in cases where products using freemium strategies face competition. In this article, we investigate how a policy by Apple on the App Store that led to stronger network effects, impacted the performance of market leaders and followers depending on whether they used freemium or not. We find that it led to an increase in revenues of leaders over followers (effectively, market dominance) but only when freemium strategies were used. The analysis demonstrates an interplay the between business model and network effects. In addition, it shows how stronger network effects and freemium strategies only benefitted market leaders in our setting.